The Development of Microlearning-Based on Teaching Materials to Increase Students’ Ecoliteracy - Nyokro Mukti Wijaya; Ahmad Yani; Nandi Nandi (JETL (Journal of Education, Teaching and Learning), 2023)
This study aims to (1) determine the validity of microlearning-based teaching materials, (2) determine the response of teachers and students to microlearning-based teaching materials, and (3) investigate the effect of microlearning-based teaching materials  on students’ ecoliteracy. The research method used was mixed research method or a combination of qualitative and quantitative approaches. The sample in this study were 63 students and 3 geography teachers at SMA Negeri 1 Belitang. The microlearning-based teaching materials developed are podcasts and videos. The results showed that (1) the results of validation tests by material experts on video teaching materials and microlearning-based podcasts  received a very high score of 81%, while the results of validation tests by media experts on video teaching materials received a very high score of 94%, and podcasts received a very high score of 96%; (2) the geography teachers’ responses to video teaching materials was very good with a score of 91.6%, and to podcast teaching materials were also very good with a score of 82.5%. While the responses of students to video teaching materials was very good with a score of 86.1%, and to podcast teaching materials were also very good with a score of 81.8%; (3) based on the results of the independent sample T-test, it is known that (a) there is an effect of using microlearning-based  video teaching materials on students’ ecoliteracy, (b) there is no effect of using  microlearning-based podcast teaching materials on students’ ecoliteracy, and (c) microlearning-based video  teaching materials have higher effectiveness than microlearning-based podcast teaching materials in influencing students’ ecoliteracy.